Evaluation of [18F]Mefway Biodistribution and Dosimetry Based on Whole-Body PET Imaging of Mice - Constantinescu, Cristian C.; Sevrioukov, Evgueni; Garcia, Adriana; Pan, Min-Liang; Mukherjee, Jogeshwar (Molecular imaging and biology, 2013)
Purpose [ 18 F]Mefway is a novel radiotracer specific to the serotonin 5-HT 1A receptor class. In preparation for using this tracer in humans, we have performed whole-body PET studies in mice to evaluate the biodistribution and dosimetry of [ 18 F]Mefway. Methods Six mice (three females and three males) received IV injections of [ 18 F]Mefway and were scanned for 2 h in an Inveon-dedicated PET scanner. Each animal also received a high-resolution CT scan using an Inveon CT. The CT images were used to draw volume of interest on the following organs: the brain, large intestine, stomach, heart, kidneys, liver, lungs, pancreas, bone, spleen, testes, thymus, gallbladder, uterus, and urinary bladder. All organ time-activity curves without decay correction were normalized to the injected activity. The area under the normalized curves was then used to compute the residence times in each organ. Data were analyzed using PMOD and Matlab software. The absorbed doses in mouse organs were computed using the RAdiation Dose Assessment Resource animal models for dose assessment. The residence times in mouse organs were converted to human values using scale factors based on differences between organ and body weights. OLINDA/EXM 1.1 software was used to compute the absorbed human doses in multiple organs for both female and male phantoms. Results The highest mouse residence times were found in the liver, urinary bladder, and kidneys. The largest doses in mice were found in the urinary bladder (critical organ), kidney, and liver for both females and males, indicating primary elimination via urinary system. The projected human effective doses were 1.21E − 02 mSv/MBq for the adult female model and 1.13E − 02 mSv/MBq for the adult male model. The estimated human biodistribution of [ 18 F]Mefway was similar to that of [ 11 C]WAY 100,635, a 5-HT 1A tracer for which dosimetry has been evaluated in humans. Conclusions The elimination of radiotracer was primarily via the kidney and urinary bladder with the urinary bladder being the critical organ. Whole-body mouse imaging can be used as a preclinical tool to provide initial estimates of the absorbed doses of [ 18 F]Mefway in humans.